The Antecedents and Consequences of Workaholism: Findings From the Modern Japanese Labor Market - Akutsu, Satoshi; Katsumura, Fumiaki; Yamamoto, Shohei (Frontiers in Psychology, 2022)
The present study examined the direct and indirect (via workaholism) relationships between competitive work environments and subjective unhealthiness. It also examined the effects of adjusting for cognitive distortions in the relationship between a competitive work environment and subjective unhealthiness and between a competitive work environment and workaholism. Data were collected from 9,716 workers in various industries, occupations, and positions. The results show that competitive work environments were positively related to subjective unhealthiness, both directly and through workaholism. Furthermore, cognitive distortions moderated the positive effect between a competitive work environment and workaholism, and the positive relationship was stronger when cognitive distortions were high (as compared to low). This study has important and practical implications for companies that are increasingly concerned about the health of their employees.